THE IMPLEMENTATION OF ISLAMIC EDUCATION IN DEVELOPING TEACHERS’ CHARACTER: A QUALITATIVE STUDY OF ISLAMIC EDUCATION TEACHERS AT SMP NEGERI 2 PADANGSIDIMPUAN - Afridah Nasution; Ahmad Subur; Zainal Efendi Hasibuan (PT. Jurnal Center Indonesia Publisher, 2026)
This study investigates the implementation of Islamic Education in fostering the character development of Islamic Education (PAI) teachers at SMP Negeri 2 Padangsidimpuan, Indonesia. Using a qualitative field study approach, data were collected through observations, semi-structured interviews, and document analysis involving PAI teachers as primary participants. The findings indicate that Islamic Education contributes significantly to strengthening teachers’ religious discipline, moral integrity, sincerity, and professional ethics. Character development is reinforced through religious habituation, exemplary conduct, and institutional support. This study offers empirical insights into the role of Islamic Education in shaping teachers’ character and contributes to the broader discourse on teacher moral development in Islamic educational contexts.